Estimating Methane Emissions From Underground Coal and Natural Gas Production in Southwestern Pennsylvania. Issue 8 (29th April 2019) - Barkley, Z. R.; Lauvaux, T.; Davis, K. J.; Deng, A.; Fried, A.; Weibring, P.; Richter, D.; Walega, J. G.; DiGangi, J.; Ehrman, S. H.; Ren, X.; Dickerson, R. R.
Abstract: Production of coal and natural gas is responsible for one third of anthropogenic methane (CH4 ) emissions in the United States. Here we examine CH4 emissions from coal and natural gas production in southwestern Pennsylvania. Using a top‐down methodology combining measurements of CH4 and ethane, we conclude that while Environmental Protection Agency inventories appear to report emissions from coal accurately, emissions from unconventional natural gas are underreported in the region by a factor of 5 (±3). However, production‐scaled CH4 emissions from unconventional gas production in the Marcellus remain small compared to other basins due to its large production per well. After normalizing emissions by energy produced, total greenhouse gas emissions from Pennsylvania unconventional natural gas production produce half the carbon footprint compared to regionally produced coal, with carbon dioxide emissions from combustion being the dominant source of greenhouse gas emissions for both sources. Key Points: Methane and ethane observations from aircraft are used to quantify methane emissions from coal and natural gas production in Pennsylvania Methane emissions from coal production align with national estimates, whereas emissions from natural gas production are underestimated Energy produced through natural gas production in Pennsylvania has half the carbon footprint compared to energy from coal mining